Benevolent and Hostile Sexism in Social Spheres: The Impact of Parents, School and Romance on Belgian Adolescents' Sexist Attitudes - Mastari, Laora; Spruyt, Bram; Siongers, Jessy (Frontiers in Sociology, 2019)
Despite growing public awareness and policy efforts, gender equality has not yet been fully established in Western societies. Previous research has shown that hostile and benevolent sexist attitudes, which are grounded in traditional gender stereotypes, play a key role in the reproduction of gender inequalities. Whereas hostile and benevolent sexism among adolescents has been previously studied, limited attention has been paid to social characteristics in understanding the support for these attitudes. In this article, we aim to study how the family, the school and romantic partnerships relate to adolescents’ benevolent and hostile sexist attitudes. We relied on data gathered in 2013 by the Flemish Youth Research Platform and performed multivariate analyses on 755 parent-child dyads (n♂ = 342; n♀ = 413). Our results indicate that social characteristics especially matter to explain the variation in benevolent sexist attitudes among girls and hostile sexist attitudes among boys. Among girls, being in a romantic relationship and parents’ traditional moral beliefs was strongly related to benevolent sexism; while for boys, hostile sexism was strongly related to being enrolled in technical and vocational education. In the conclusion, we elaborate on the implications of our findings.